In The Growth of Islamic Education, Alkhairaat - Sutijah; An An Andari; Afif Ansori (EduInovasi: Journal of Basic Educational Studies, 2024)
The purpose of this paper is to outline the evolution of Islamic education in Boalemo under Alkhairaat. This kind of research is qualitative and uses wawacnara, documentation, and observation as data gathering methods. The findings demonstrated that the emergence and expansion of Alkhairaat in Gorontalo was preceded by its existence in Boalemo (Tilamuta) in 1967. From the inception to the present, Alkhairaat has undergone continuous development and improvement, leading the way in education from kindergarten/TPA to college. Boalemo's education system is developing Alkhairaat in five subdistricts, each of which has a different educational institution than TK-MA. The society has responded favorably to Alkhiraat's role as the coordinator of Islamic religious instruction, and it has since become the cornerstone for the society and thought to be able to satisfy the religious demands of the general public as well as the educational needs of the younger generation in particular.